Trocas de energia e massa no cultivo de soja e trigo no sul do Brasil - Veeck, Gustavo Pujol (2018)
Brazil is one of the largest agricultural producers in the world. With this, a vast area of Brazilian territory is covered by crops that directly influence the annual carbon balance and the exchange of water vapor between the Earth’s surface and the atmosphere. It is fundamental to understand how the net exchanges of water and energy correspond to changes in environmental and biological variables and what mechanisms control them. In this work the relations between the energy and mass exchanges between the surface and the atmosphere were analyzed with the environmental variables of pressure vapor pressure (VPD), air temperature (temp), relative humidity (RH) and incident global radiation (Rg) in a commercial system of crop rotation, wheat in the winter and soybean in the summer, located in the municipality of Carazinho in the state of Rio Grande do Sul, Brazil. Gross primary production (GPP) was used to compute the atmospheric fluxes, the partitioning of the SEN into gross primary production (GPP), using the Eddy Covariance (EC) and respiration of the ecosystem Reco. Analysis of the flux data of CO2 using EC for wheat and rainfed soybeans shows that both behaved as an absorber of CO2 and wheat, from 35 days after emergence, absorbed 287.61 (C-CO-2) m-2, while the complete cycle of soybean absorbed 209.20 g(C — CO — 2) m⁻². ET for the same period as wheat was 279.19 mm and for soy was 428.15 mm. The hysteresis relationships formed between the NEE and latent heat flux (LE) were characterized with the environmental variables VPD, temp, RH and Rg for the different phases of the crops. The shape and the areas of the hysteresis show how the environmental flows vary in the average daily cycle in the different phenological phases of the plants. Areas of the hysteresis were larger for the stages of higher crop development, and generally larger for soybean. The results obtained here can be used both for the analysis of the simulations of agricultural and climatic models as well as, forcing of initialization of these